Salon in crisis: tensions between tradition and rupture in the 1919 Salon - Vassoler, Vanessa Pereira; Lopes, Almerinda da Silva (Revista do Colóquio, 2025)
In his chronicle dedicated to the 1919 National Salon of Fine Arts, Antônio Vieira da Cunha sharply criticizes the rigidity of the academicism of the National School of Fine Arts, whose permanence compromised the vitality of Brazilian art. Observing a panorama of creative stagnation, the author denounces the attachment of generations of artists to exhausted European models, revealing a scenario in which formal repetition stifles any possibility of expressive renewal. In contrast to this mimicry, he defends the urgency of looking at the singularity of the landscape and national culture, pointing out in them a fertile potential for more authentic artistic languages. Vieira da Cunha highlights the limitations of the ENBA's pedagogical model, whose excessive emphasis on technique stifles creative freedom and makes the formation of autonomous artistic thought impossible.
Keywords: Vieira da Cunha; 1919 Salon of Fine Arts; Art Criticism